PTH-264 Preoperative chemoradiotherapy does not appear to have short-term effects on human rectal neuromuscular functions. (22nd June 2015) - Kung, V; Broad, J; Machesney, M; Thaha, M; Knowles, C; Sanger, G
Abstract : Introduction: Preoperative chemoradiotherapy may impair anorectal functions. Its effect on neuromuscular functions was investigated in human rectum ex-vivo . Method: Following informed consent, 3 groups of patients undergoing surgery for anorectal cancer were studied: 13 patients treated by surgery alone (Group I); 13 with long course neoadjuvant chemoradiotherapy (capecitabine) (Group II); and 4 with prior platinum-based chemoradiotherapy (oxaliplatin/capecitabine n = 2, FOLFOX/capecitabine n = 1, carboplatin/paclitaxel n = 1) (Group III). Age and gender were similar between Group I and II. Group III [55 (range=51–60)] were younger than Group I [72 (range=50–87)]. Postoperatively, macroscopically-normal rectum (without taenia) was obtained 5–10cm away from tumour. Mucosa-free circular muscle strips were suspended in tissue baths for isometric recording and electrical field stimulation (EFS, 1–20Hz, 50V, 0.5ms, for 10s) applied. 1 Data are expressed as median (inter-quartile range) and analysed using ANOVA with multiple comparison post-tests. Results: EFS usually caused contraction (or relaxation at low frequencies), often followed by an 'after-contraction' on termination. Amplitudes of contractions during and after EFS, and area under curve (AUC) of the full muscle movement increased with frequency (see table ). Contractions were abolished by atropine 1 µM and tachykinin (NK1–3 ) receptor antagonists (n = 4) and greatly reduced by the neurotoxin tetrodotoxin 1 µM (n = 2). All parameters of the movements evoked by EFS at all frequencies [AUC, amplitude of responses during EFS and after EFS] were similar amongst the 3 groups. There were no significant differences in tension generated by carbachol 10 µM (maximally-effective concentration) between groups (see Table 1, P > 0 .05 for all measurements). Conclusion: In this pilot study, preoperative chemoradiotherapy with capecitabine or platinum-based agents does not appear to have short-term effects on human rectal neuromuscular function. Reported impairment of anorectal function may be due to its long term effects or via other mechanisms. Disclosure of interest: V. Kung Grant/ Research Support from: AgeUK PhD studentship, Barts and the London Charity, J. Broad: None Declared, M. Machesney: None Declared, M. Thaha: None Declared, C. Knowles: None Declared, G. Sanger Grant/ Research Support from: Takeda. Reference: Broad et al . Br J Pharmacol. 2013;179:1253–61